A population balance model to modulate shear for the control of aggregation in Taxus suspension cultures. (8th November 2019) - Wilson, Sarah A.; Maindarkar, Shashank N.; McKee, Michelle C.; Vilkhovoy, Michael; Henson, Michael A.; Roberts, Susan C.
Abstract: Cellular aggregation in plant suspension cultures directly affects the accumulation of high value products, such as paclitaxel from Taxus . Through application of mechanical shear by repeated, manual pipetting through a 10 ml pipet with a 1.6 mm aperture, the mean aggregate size of a Taxus culture can be reduced without affecting culture growth. When a constant level of mechanical shear was applied over eight generations, the sheared population was maintained at a mean aggregate diameter 194 μm lower than the unsheared control, but the mean aggregate size fluctuated by over 600 μm, indicating unpredictable culture variability. A population balance model was developed to interpret and predict disaggregation dynamics under mechanical shear. Adjustable parameters involved in the breakage frequency function of the population balance model were estimated by nonlinear optimization from experimentally measured size distributions. The optimized model predictions were in strong agreement with measured size distributions. The model was then used to determine the shear requirements to successfully reach a target aggregate size distribution. This model will be utilized in the future to maintain a culture with a constant size distribution with the goal of decreasing culture variability and increasing paclitaxel yields.